2021
DOI: 10.48550/arxiv.2112.13591
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Unveiling the nature of 12 new low-luminosity Galactic Globular Cluster Candidates

E. R. Garro,
D. Minniti,
B. Alessi
et al.

Abstract: Context. The Galactic globular cluster system is incomplete, especially in the low latitude regions of the Galactic bulge and disk. We report the physical characterization of twelve star clusters in the Milky Way, most of which are explored here for the first time. Aims. Our primary aim is determining their main physical parameters, such as reddening and extinction, metallicity, age, total luminosity, mean cluster proper motions (PMs), distances, in order to unveil the physical nature of these clusters. Method… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…To compute the orbits of Patchick 125 we adopted the following three initial conditions: (i) The mean proper motions for Patchick 125 were adopted from the values determined by Garro et al (2021c), that is, µ α = −3.85 ± 0.50 and µ δ cos(δ) = +0.64 ± 0.39; (ii) Garro et al (2021c) measured distances of D = 11.2 kpc and 10.9 kpc to this GC based on the optical and NIR CMDs, respectively. They also identified two RR Lyrae variable stars as cluster members based on their matching positions, magnitudes, and Gaia proper motions.…”
Section: Orbitmentioning
confidence: 99%
See 1 more Smart Citation
“…To compute the orbits of Patchick 125 we adopted the following three initial conditions: (i) The mean proper motions for Patchick 125 were adopted from the values determined by Garro et al (2021c), that is, µ α = −3.85 ± 0.50 and µ δ cos(δ) = +0.64 ± 0.39; (ii) Garro et al (2021c) measured distances of D = 11.2 kpc and 10.9 kpc to this GC based on the optical and NIR CMDs, respectively. They also identified two RR Lyrae variable stars as cluster members based on their matching positions, magnitudes, and Gaia proper motions.…”
Section: Orbitmentioning
confidence: 99%
“…In this paper we present near-infrared (NIR) elemental abundances of the heavily obscured (E(B − V) ∼ 1.06; Garro et al 2021c) GC Patchick 125 (originally discovered by Dana Patchick in 2016, internal communication) toward the Galactic bulge, which is positioned within 10.2 of the centre of the GC Gran 3 (Gran et al 2022), so both clusters are the same, and from here on we refer to this cluster as Patchick 125.…”
Section: Introductionmentioning
confidence: 99%
“…First, we performed a decontamination procedure which allowed us to build clean CMDs and construct final catalogues with probable star cluster members. The decontamination of this dataset follows the one described by Garro et al (2020Garro et al ( , 2021a. As mentioned in Section 3, we excluded all nearby stars, through a cut in parallax.…”
Section: Decontamination Procedures and Cluster Membershipmentioning
confidence: 99%
“…The Gaia mission (e.g. Cantat-Gaudin et al 2019;Castro-Ginard et al 2020) is extremely helpful in that endeavour and has in fact confirmed many of the recently discovered star clusters as GCs, some examples include the following: Garro 01 (Garro et al 2020), FSR 1758 (Barbá et al 2019;Villanova et al 2019;Romero-Colmenares et al 2021), Patchick 99 (Garro et al 2021c), Patchick 125 (Fernández-Trincado et al 2022;Garro et al 2021a, named also Gran 3 by Gran et al 2022), and VVV-GC160 (Minniti et al 2021a;Garro et al 2021d); another nine GCs confirmed by Garro et al (2021d), FSR 19 and FSR 25 (Obasi et al 2021), and Minni48 (Minniti et al 2021c); and another five GCs confirmed in Garro et al (2021a). These studies as well as other ones are fundamental since they can contribute, from a broad point of view, for one to understand the formation and evolution of the MW GC system.…”
Section: Introductionmentioning
confidence: 99%